Blast resistance of small-scale RCS in experimental test and numerical analysis. (15th November 2019) - Zhao, Chunfeng; Wang, Qiang; Lu, Xin; Huang, Xinghai; Mo, Y.L.
Highlights: Experimental and numerical study on the blast performance of the RCSs. Failure patterns and maximum deflections of RCS are investigated. There are three types of failure modes in the RCSs under blast loads. The accuracy of the FE model is verified by the experimental test. Abstract: Experimental and numerical studies are conducted to investigate the blast behavior of small-scale reinforced concrete slab (RCS), which is proposed to overcome the disadvantage of the previous studies without verification. A three-dimensional finite element model is established with validated material parameters, blast load model and reasonable choice of boundary conditions. Three small-scale RCSs are designed and cast, two RCS are subject to the explosion at a scaled distance of 0.611 m/kg 1/3 and another RCS is subjected to blast load at a scaled distance of 0.77 m/kg 1/3 to calibrate and validate the finite element model. The experimental results of damage area and linear variable differential transformers (LVDTs) are analyzed and compared with finite element analysis prediction. The comparison indicates that the failure patterns of these slabs are categorized as three types, including the low damage, moderate damage and severe damage in both experimental tests and numerical simulations. In addition, the numerical results of RCSs are consistent with test results, except for the formation of cracks, which demonstrates that the blast-resistant capacities of RCSs can improve with the reinforcement ratio increasing and the explosive charges decreasing.